Effect of Infill Density in FDM 3D Printing on Low-Cycle Stress of Bamboo-Filled PLA-Based Material - Müller, Miroslav; Jirků, Petr; Šleger, Vladimír; Mishra, Rajesh Kumar; Hromasová, Monika; Novotný, Jan (Polymers, 2022)
In this paper, the fatigue behavior of polylactic acid (PLA) material with bamboo filler printed by 3D additive printing using fused deposition modelling (FDM) technology at different infill densities and print nozzle diameters is investigated. The mechanical test results are supported by the findings from SEM image analysis. The fatigue behavior was tested at four consecutive 250 cycles at loads ranging from 5 to 20, 30, 40, and 50% based on the limits found in the static tensile test. The results of the static tensile and low-cycle fatigue tests confirmed significant effects of infill density of 60%, 80%, and 100% on the tensile strength of the tested specimens. In particular, the research results show a significant effect of infill density on the fatigue properties of the tested materials. The influence of cyclic tests resulted in the strengthening of the tested material, and at the same time, its viscoelastic behavior was manifested. SEM analysis of the fracture surface confirmed a good interaction between the PLA matrix and the bamboo-based filler using nozzle diameters of 0.4 and 0.6 mm and infill densities of 60%, 80%, and 100%. Low-cycle testing showed no reductions in the mechanical properties and fatigue lives of the 3D printed samples.
Keywords: bamboo; infill density; PLA polymer; mechanical properties; SEM; 3D printing; low-cycle test